Butte Paper - Preparation of Ore Containing Zinc for the Recovery of Other Metals, Such as Silver, Gold, Copper, and Lead, by the Elimination and Subsequent Recovery of the Zinc as a Chemically Pure Zinc Product (with Discussion) - S. E. Bretherton (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1914)
This title introduces the subject I wish to describe to my fellow members, very few of whom, I 'hope, have ever had as much trouble with the smelting of ore containing much zinc, either in the lead blast furnace or the matting furnace, as circumstances have forced upon me: First, for several years in Leadville, Colo., after the sulphide ores containing zinc had been developed with greater depth and were sold to the intereats with which I was connected for smelt-ing in the blast furnace for the recovery of the lead, silver, and gold; then, in New Mexico and Arizona, where the principal source of ore supply for our custom smelter was from miners who sent most of their product in the form of concentrates, which we briquetted and smelted in the blast furnace, producing a matte containing copper, silver, and gold, for which we were paid; together with some zinc and lead, which was penalized if in excess of a maximum base set by the refinery to which we sold our copper matte; last, but not least, my experience in Shasta county, Gal., where for the sake of recovering $13 per ton value in copper, silver, and gold, I have smelted ore containing as high as 40 per cent. zinc (the last 18,951 tons smelted averaged 15 3/10 per cent. zinc) which we not only lost, but which it cost us money to lose. After such an experience, and knowing that, instead of being worth only $13 per ton, such 15 per cent. zinc ore should be worth about $30, including zinc at the present market value, the question of recovering the zinc in a profitable manner from such ore became very interesting to me. During several years' time I sent samples, of from 5 to 1,200 lb. each, to be tested by the different best-known zinc-recovery plants, and experimented with several processes proposed by others for the treatment of such ore, with but little encouragement, until I